Bearing press / Mohd Yazid Bahari - Bahari, Mohd Yazid; Abdullah, Mohd Firdaus; Ranom, Rahizal; Shafea@Shafie, Ahmad Ridduan (2005)
The Final Year Project is one of the subjects for all the final year students of Diploma in Mechanical Engineering to complete their diploma. The purposes of this subject to expose the students with the equipment in the workshop watch over by the supervisors. This subject also train student on how to produce product within the required time, how to work in-group and how to produce a product in a manage situation. In this subject, Student will have to produce a product base on what they have studied. The product can be anything that inner contact with mechanical engineering. This report contents the process of our project named as "bearing press". The processes clearly explained in chapter two of this report. We have done some investigation and research for this product. We found that this product is practical to produce base on some factor like this press bearing can easily to press bearing without any misalignment during bearing installation. In other words, it is too much better than hammer the bearing. It is because when we use a hammer, the bearing may be damage. So, we are sure this product will begetting practical to use. At the end of this report we only include result and discussion, application and conclusion of the project.